Endothelial cell GATA2 modulates the cardiomyocyte stress response through the regulation of two long non-coding RNAs - Froese, Natali; Szaroszyk, Małgorzata; Korf, Mortimer; Koch, Katrin; Schmitto, Jan Dieter; Geffers, Robert; Hilfiker-Kleiner, Denise; Riehle, Christian; Wollert, Kai Christoph; Bauersachs, Johann; Heineke, Jörg (Biology, 2022)
Capillary endothelial cells modulate myocardial growth and function during pathological stress, but it is unknown how and whether this contributes to the development of heart failure. We found that the endothelial cell transcription factor GATA2 is downregulated in human failing myocardium. Endothelial GATA2 knock-out (G2-EC-KO) mice develop heart failure and defective myocardial signal transduction during pressure overload, indicating that the GATA2 downregulation is maladaptive. Heart failure and perturbed signaling in G2-EC-KO mice could be induced by strong upregulation of two unknown, endothelial cell-derived long non-coding (lnc) RNAs (AK037972, AK038629, termed here GADLOR1 and 2). Mechanistically, the GADLOR1/2 lncRNAs transfer from endothelial cells to cardiomyocytes, where they block stress-induced signalling. Thereby, lncRNAs can contribute to disease as paracrine effectors of signal transduction and therefore might serve as therapeutic targets in the future.